Gas-sensitive properties of individual carbon nanotubes modified by ion and electron irradiation - N. A. Davletkildeev; E. Yu. Mosur; I. A. Lobov (Омский научный вестник)
The time characteristics of resistance change of individual nitrogen-doped multi-walled carbon nanotubes (N-MWCNTs), initial and irradiated with electrons, protons and argon ions has been measured upon exposure to ammonia and nitrogen dioxide. It is found that the initial N-MWCNTs have n-type conductivity, N-MWCNTs irradiated with protons and argon ions have p-type conductivity, and those irradiated with electrons have n-type conductivity. The relative gas sensitivity of individual N-MWCNTs, initial and irradiated with ions and electrons, has been determined.